Sustainability in the Portuguese agricultural sector: Assessment and multicriteria approach - Ana Marta-Costa (Economía Agraria y Recursos Naturales)
Based on data available between 2016 and 2021 from the Portuguese FADN, fifteen sustainable indicators were measured, and a compromise programming model was designed to balance environmental and economic objectives, that reveal a conflict between them. The findings identified solutions dominated by dried fruits, olive trees, sheep and goats, extensive horticulture, and beef cattle for sustainable farming planning at the national level. We conclude that the complementary between these two approaches constitute an important instrument for supporting decision-making and developing public policies focused on current sustainability paradigms.